Narrative Review: Factors Associated with the Sexually TransmittedInfections (STIs) Among Tugboat Crews in the Mahakam River - Nunuk Kusuma Wardani; Irfansyah Baharuddin Pakki; Akhmad Azmiardi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Sexually transmitted infections (STIs) remain a persistent global health concern, particularly among maritime workers such as tugboat crews. Prolonged sailing periods, limited healthcare access, and high-risk sexual behavior increase their vulnerability to infection. This narrative review aims to summarize key determinants influencing STI risks and prevention behaviors among tugboat crews in the Mahakam River area. Objective : This review seeks to identify and analyze the main determinants related to STI occurrence among tugboat crews, focusing on individual, social, and environmental aspects. The objectives include describing individual factors such as knowledge, attitude, and sexual behavior; exploring social and environmental determinants like social support, access to health services, and working conditions; and synthesizing evidence-based recommendations for strengthening STI prevention programs among maritime workers. Research Methods/ Implementation Methods : Articles published between 2019 and 2025 were collected from PubMed and Google Scholar using keywords related to STIs, sailors, fishermen, and port workers. Thirty eligible studies in English were analyzed narratively to identify consistent determinants influencing STI prevention and risk. Results : The review revealed that low sexual health knowledge, negative attitudes toward STI prevention, and risky sexual behaviors are the dominant contributing factors. Additional barriers include stigma, cultural norms restricting sexual health discussion, and limited routine health screening among seafarers. These conditions increase vulnerability to STIs and hinder prevention efforts. Conclusion/Lesson Learned : Tugboat crews on the Mahakam River face elevated risks of STIs due to behavioral, social, and structural challenges. Integrated approaches involving education, access to health services, and supportive policies are essential for effective STI prevention. This review provides evidence to guide targeted interventions and policy development in maritime health programs.